Enhancement of the Photoresponse in Organic Field‐Effect Transistors by Incorporating Thin DNA Layers1. (18th November 2013) - Zhang, Yuan; Wang, Mingfeng; Collins, Samuel D.; Zhou, Huiqiong; Phan, Hung; Proctor, Christopher; Mikhailovsky, Alexander; Wudl, Fred; Nguyen, Thuc‐Quyen
Abstract A mechanistic study of the DNA interfacial layer that enhances the photoresponse in n‐type field‐effect transistors (FET) and lateral photoconductors using a solution‐processed fullerene derivative embedded with disperse‐red dye, namely PCBDR, is reported. Incorporation of the thin DNA layer simultaneously leads to increasing the electron injection from non‐Ohmic contacts into the PCBDR active layer in dark and to increasing the photocurrent under irradiation. Such features lead to the observation of the enhancement of the photoresponsivity in PCBDR FETs up to 103. Kelvin probe microscopy displays that in the presence of the DNA layer, the surface potential of PCBDR has a greater change in response to irradiation, which is rationalized by a larger number of photoinduced surface carriers. Transient absorption spectroscopy confirms that the increase in photoinduced carriers in PCBDR under irradiation is primarily ascribed to the increase in exciton dissociation rates through the PCBDR/DNA interface and this process can be assisted by the interfacial dipole interaction.